Une poétique de la dissimulatio ou l’entre-deux de Théesée au livre 12 de la Thébaïde de Stace - Tola, Eleonora (2020)
The role of Theseus in the closure of Statius’ Thebaid has been the subject of much debate. The positive readings of the character’s intervention in the poem’s last scene coexist with interpretations that show, rather, some darker aspects of the character, which relate to his Catullian and elegiac tradition. Certainly, scholars have also identified the ambiguities underlying the inclusion of Theseus at the end of the poem within the political context of Statius’ writing. In fact, although detached from Roman history through its mythic content, this Flavian epic involves the problem of the limits and the risks of autocracy. It is in such a “negotiation” of discourses that I envision my reading of this section of the Thebaid. From a stylistic approach, I aim to disclose the poetic effects of its ambivalences in light of the whole poem.